2007
DOI: 10.1002/hec.1260
|View full text |Cite
|
Sign up to set email alerts
|

Spending to save? State health expenditure and infant mortality in India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
73
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 31 publications
9
73
0
3
Order By: Relevance
“…While Makela et al (2013) found negative association between social sector spending and child mortality, 18 Deolalikar (2005) found a weak relationship. 16 Bhalotra (2007) found the negative association between public health spending and infant mortality only in rural areas. 17 The findings of these studies might have got affected by choice of the analysis and the sample size.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…While Makela et al (2013) found negative association between social sector spending and child mortality, 18 Deolalikar (2005) found a weak relationship. 16 Bhalotra (2007) found the negative association between public health spending and infant mortality only in rural areas. 17 The findings of these studies might have got affected by choice of the analysis and the sample size.…”
mentioning
confidence: 98%
“…16 Bhalotra (2007) found the negative association between public health spending and infant mortality only in rural areas. 17 The findings of these studies might have got affected by choice of the analysis and the sample size.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Government health expenditure in India is relatively low compared to other countries in the region and has actually declined over the last two decades. According to Bhalotra (2007), while government health expenditure constituted 1.3% of the GDP in 1990, this had declined to 0.9% in 1999. Relative to other countries in the region, India devotes a smaller share of its income to health spending than, for example, Bangladesh (1.4%) or Sri Lanka (1.8%) (Deolalikar 2005), and it spends a disproportionate part of its health budget on (curative) hospital services which are less pro-poor than (preventive) public health expenditures (Peters et al 2002).…”
Section: Review Of Health Management Aspects Of Icdsmentioning
confidence: 99%